Pelatihan Manajemen Keuangan dan Pentingnya Dana Darurat dalam Menghadapi Ketidakpastian pada Masyarakat Banyumas - Eka Tripustikasari (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Financial management can improve financial management well and have an impact in the future, including future threats that cannot be predicted to be able to face emergency funds. Emergency funds can provide a sense of security to face events that cannot be predicted in advance. The aim of this training is to increase insight into emergency funds among the Banyumas community, especially for customers of state-owned banks in Banyumas Regency branches. From this training it can be concluded that financial management has an important role in the financial management process, both sources of income and expenditure management. And it was also found that 97% of the 34 participants felt that emergency funds were important, but only 20 people currently had emergency funds.